Sexual hormones levels in pre and post-partum preeclamptic and healthy normotensive pregnant women - Rondón-Tapía, Marta (2017)
Objective: To compare pre and post-partum sexual hormones concentrations in preeclamptic patients and in healthy normotensive pregnant women. Design: Casecontrol study. Setting: Hospital Central “Dr. Urquinaona”, Maracaibo, Venezuela. Participants: Normotensive and preeclamptic pregnant women. Methods: A total of 142 patients were selected. Ninety preeclamptic patients were selected as the study group (group A) and 71 healthy normotensive pregnant women with similar age and weight were selected as controls (group B). Blood samples were extracted from all patients before labor and immediately after diagnosis in group A to determine sexual hormones concentrations. Post-partum follow-up samples were collected at 7 days and 6 weeks later in both groups. Main outcome measures: General characteristics, concentrations of total testosterone, free testosterone, dehydroepiandrosterone sulfate, androstenedione and estradiol. Results: Significant differences in concentrations of all sexual hormones (p < 0.0001) were found in the pre-partum period between both groups, except in androstenedione values (p = 0.0917). All sexual hormones levels showed significant differences between both groups at 7 days after delivery post-partum (p < 0.0001). At 6 weeks postpartum, all sexual hormones presented significant differences between groups (p < 0.0001), with the exception of total testosterone (p = 0.2479). Conclusion: There were significant differences in pre and post-partum sexual hormone concentrations between preeclamptic patients and normotensive pregnant women.